Polypharmacy behavior: an aspect to be taken into consideration. - Senén Rodríguez Fernández; Sahily García Ledo; Maritza Almeida Torregrosa (Medisur)
Fundament: While medications are more sophisticated, their actions are wider as well as their undesirable reactions. If we use two drugs we will be duplicating the possibilities of their effects desired to benefit the patients, but also the adverse reactions. Objectives: To characterize the polypharmacy behavior in the internal medicine service at the university hospital ¨Dr. Gustavo Aldereguía Lima¨ in Cienfuegos, Cuba. Methods: A descriptive study which includes a review of all the medications used according to the disease and the patient. It was carried out in a group of 200 patients admitted at the internal medicine service at the university hospital ¨Dr. Gustavo Aldereguía Lima¨ in Cienfuegos from January 2004 to February 2005. The data were collected from an interview which included the admission chief complaint and the medications used. Results: There were no differences between both sexes. The majority of patients were elderly. The usage of multiple medications was remarkable, in some cases 11 and even 13 drugs were used simultaneously. A tendency to use more than 5 medications per patients was observed. Conclusions: We should be more rational with the number of medications used simultaneously in a patient, even more with elder patients who are the most representative number of patients in our medical assistance centre